Analisis Implementasi Peraturan Gubernur Sumatera Utara No. 29 Tahun 2020 dalam Tugas Kelembagaan - Saputra, M. Fernanda; Muda, indra; Kurniaty, Evi Yunita (Universitas Medan Area, 2024)
Policy implementation is an important stage in achieving the program objectives that have been set. This study aims to evaluate the implementation of North Sumatra Governor Regulation (Pergubsu) No. 29 of 2020 in the Institutional and Position Analysis Section of the Organization Bureau of the Regional Secretariat of North Sumatra Province and identify inhibiting factors in the process. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Respondents consisted of Section Heads, Sub-Section Heads, and executive position employees in the Institutional and Position Analysis Section. The results showed that the implementation of Pergubsu No. 29 of 2020 has not been optimal because there are still several obstacles, such as a lack of adequate human resources, a heavy workload, and a limited budget for the Job Analysis Subdivision. In addition, technical infrastructure such as computers and printers are also inadequate for administrative needs. Therefore, measures are needed to improve policy implementation, including increasing human resources, adequate budget allocation, and improving technical infrastructure.